Image Quality and Detection of Small Focal Liver Lesions in Diffusion-Weighted Imaging: Comparison of Navigator Tracking and Free-Breathing Acquisition. Issue 9 (September 2021) - Saake, Marc; Seuß, Hannes; Riexinger, Andreas; Bickelhaupt, Sebastian; Hammon, Matthias; Uder, Michael; Laun, Frederik B.
Abstract : Objectives: The aim of this study was to compare intraindividual diffusion-weighted imaging (DWI) of the liver acquired with free breathing (FB) versus navigator triggering (NT) for assessing small focal liver lesions (FLLs) in noncirrhotic patients. Materials and Methods: Patients with known or suspected multiple FLLs were prospectively included, and spin-echo echo-planar DWI with NT and FB acquisition was performed (b-values, 50 and 800 s/mm 2 [b50 and b800]). NT and FB DWI sequences with similar acquisitions times were used. Liver and lesion signal-to-noise ratios were measured at b800. The DWI scans were analyzed independently by 2 readers. Liver edge delineation, presence of stair-step artifacts, vessel sharpness, severity of cardiac motion artifacts, overall image quality, and lesion conspicuity were rated with 5-point Likert scales. Small and large FLLs (ie, <1 cm or ≥1 cm) were rated separately for lesion conspicuity. The FLL detectability was estimated by comparing the number of lesions visible with FB to those visible with NT. Results: Forty-three patients were included in the study. The FB acquisition performed better in terms of severity of cardiac motion artifacts. The NT performed better in terms of liver edge delineation and vessel sharpness. Little difference was found for stair-step artifact, overall image quality, and conspicuity of large FLL, whereas the conspicuity of small FLL was better for NT. For small FLL, both readers found more lesions with NT in 11 cases at b800. For large FLL, this effect was much less pronounced (1 case at b800 reported by 1 of the readers). The mean liver and lesion signal-to-noise ratios were 16.8/41.5 and 19.8/38.4 for NT/FB, respectively. Conclusions: Small FLL detection is better with NT. Large FLL detection by FB and NT is similarly good. We conclude that NT should be used.